Peningkatan Keterampilan Menulis Teks Eksposisi Dengan Menggunakan Strategi Pembelajaran Berbasis Proyek - Sofian, Azwandi; Asri, Aswati; Sulaiman, Miming Salmah (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the application of project-based strategies in improving exposition text writing skills of class X SMA Negeri 10 Gowa students. The research used Classroom Action Research method which was conducted in two cycles. The subjects of the research were students of class X SMA Negeri 10 Gowa totalling 30 students. Data collection techniques included observation sheets, writing tests, interviews with students, and documentation to support the research results. The research instruments consisted of tests and non-tests. The data obtained were analysed using qualitative and quantitative descriptive techniques. The results showed a significant improvement in students' exposition text writing skills from the first cycle to the second cycle. In the first cycle, the students' completion rate only reached 40%, with an average score of 72. Most students still had difficulty developing ideas, using good grammar, and understanding the appropriate writing structure. In the second cycle, after revising the approach with more intensive guidance, the completion rate increased to 93%, with an average score of 85. This increase shows that the project-based strategy is effective in improving students' exposition text writing skills. This approach not only helps students understand the structure of writing, but also involves them in the creative process of writing, increasing motivation, and a sense of responsibility for their work. Based on the results of the study, the project-based strategy is recommended to be widely applied in writing learning at the senior high school level.